Tailings and mine waste '04 : proceedings of the Eleventh Tailings and Mine Waste Conference, 10-13 October 2004, Vail, Colorado, USA.: proceedings of the Eleventh Tailings and Mine Waste Conference, 10-13 October 2004, Vail, Colorado, USA. (©2004) - Unknown
No abstract available